EVALUATION OF MACULAR ISCHEMIA IN EYES WITH CENTRAL RETINAL VEIN OCCLUSION: An Optical Coherence Tomography Angiography Study. Issue 8 (August 2018) - Ghashut, Rima; Muraoka, Yuki; Ooto, Sotaro; Iida, Yuto; Miwa, Yuko; Suzuma, Kiyoshi; Murakami, Tomoaki; Kadomoto, Shin; Tsujikawa, Akitaka; Yoshimura, Nagahisa
Abstract : Purpose: To quantitatively assess macular perfusion status using optical coherence tomography angiography in eyes with aflibercept-treated central retinal vein occlusion and resolved macular edema and to investigate the impact of macular morphology and perfusion status on visual function. Methods: This prospective consecutive case series included 23 patients with central retinal vein occlusion. All patients received intravitreal aflibercept injections before analysis. Visual acuity, macular sensitivity, and the macular nonperfusion area (NPA) were evaluated in eyes without macular edema. The macular NPA was evaluated by optical coherence tomography angiography using 3 mm × 3 mm images of the macula. Foveal ellipsoid zone disruption was also analyzed. Results: The superficial macular NPA measured 4.15 mm 2 ± 0.71 mm 2 (95% confidence interval 3.85–4.46), and the deep macular NPA measured 4.23 mm 2 ± 0.97 mm 2 (95% confidence interval 3.82–4.56). The logarithm of the minimum angle of resolution visual acuity was significantly associated with foveal ellipsoid zone disruption ( P = 0.001), the superficial macular NPA ( P = 0.015), and the deep macular NPA ( P = 0.018). Macular sensitivity correlated negatively with logarithm of the minimum angle of resolution visual acuity ( P = 0.007), the superficial macular NPA ( P = 0.029), and the deep macular NPA ( P = 0.040), but not with the foveal ellipsoid zone disruption ( P = 0.435). Conclusion: Optical coherence tomography angiography is a novel technique that enables segmented evaluation of the macular perfusion status in eyes with central retinal vein occlusion and provides visual prognostic information. Enlargement of the macular NPA in the superficial and deep layers was significantly correlated with impaired visual acuity and with decreased macular sensitivity in patients with aflibercept-treated central retinal vein occlusion and resolved macular edema. Abstract : Supplemental Digital Content is Available in the Text.Enlargement of the macular nonperfusion area was significantly correlated with impaired visual acuity and decreased macular sensitivity in patients with central retinal vein occlusion without macular edema.